The Development of Taro Processed Product in Women Farmers Group in Baru Village, Tabanan Bali Indonesia - Luh Suriati; Aida Firdaus Muhamad Nurul Azmi; Raseetha Vani Siva Manikam; Ni Made Ayu Suardani Singapurwa; I Gede Pasek Mangku; Anak Agung Made Semariyani; I Wayan Sudiarta; I Nyoman Rudianta; I Putu Candra; Ni Luh Putu Putri Setianingsih (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2022)
The processing of food products during the pandemic is growing rapidly, resulting in processed products that are increasingly diverse and widespread in the market. To empower rural communities by improving knowledge, attitudes, skills, and behaviors, activities and mentoring programs are needed in accordance with the needs of the community. This community service activity was held in the Group of Women's Farmers “Dharma Santi”, Baru Village, Marga Sub district, Tabanan Regency, Bali Province. Taro is an untapped commodity in Baru Village. Processing taro into various products such as bread, jam, and noodles have been produced and marketed by Women Farmers Group, but marketing is still limited around the village. Farmers Group does not have adequate entrepreneurship skill, production management, and marketing. The solution to address partner problems is to provide the right technology for processing bread, jam, and taro noodles, equipment assistance, knowledge of packaging and product labeling, marketing, and entrepreneurship. The implementation of community service activities has been running smoothly. The number of participants who participated in the activity was 10 people. Based on the results of the evaluation, this group mastered the technology of making bread, jam, and taro noodles up to 75%. Further help is needed to the group so that more quality bread products, jams, and taro noodles produced have a longer shelf life as well as wider marketing.